THE RELATIONSHIP OF PARENTING PATTERNS WITH LEARNING OUTCOMES OF STUDENTS OF CLASS V ELEMENTARY SCHOOL INPRES 1 DONGGULU - Azizah Thalib; Ria Utami Hairullah (Universitas PGRI Yogyakarta, 2022)
This study aims to determine the relationship between parenting styles and student learning outcomes in grade V SD Inpres 1 Donggulu as well as differences in the average student learning outcomes of the three types of parenting. The parenting style in question is authoritarian, democratic and permissive upbringing. This study uses a quantitative type of experimental research method. The sample in this study were students of class V. The data collection techniques used were questionnaires and documentation. The data obtained were analyzed using correlation test and ANOVA test. The results of data analysis show that: (a) the significance value of authoritarian parenting is greater than 0.05 (0.600 > 0.05), (b) the significance value of democratic parenting is greater than 0.05 (0.442 > 0.05), and ( c) the significance value of permissive parenting is greater than 0.05 (0.862 > 0.05). So Ho is accepted and Ha is rejected, meaning that there is no relationship between parenting styles and student learning outcomes in grade V SD Inpres 1 Donggulu. The results of data analysis using one way ANOVA show that the significance value 0.137>0.05, which means that the average student learning outcomes of the three parenting styles are